Paper Retracted - IMPACT OF FATHER’S EMIGRATION ON THE EDUCATIONAL TRENDS OF CHILDREN LEFT BEHIND - Saeed, Yasir; Raza, Hassan (European Scientific Journal, ESJ, 2015)
Due to an authorship dispute, under a mutual agreement this paper has been retracted. ESJ editorial office May 2016